Effect of Ethanol Extract of Red Beetroot (Beta vulgaris L.) on the Follicle Stimulating Hormone Levels among Wistar Rats (Rattus norvegicus) Exposed to Cigarette Smoke - Intiyaswati; Sofyan H Nur; Ethyca Sari (EMBRIO: Jurnal Kebidanan, 2022)
Ethanol extract of red beetroot (Beta Vulgaris L.) contains chemical compounds of ascorbic acid, carotenoite, phenolic acid, betalain, and favonoids. Red beetroot supplements can prevent oxidative damage to the structure of DNA, lipids and proteins in vitro. This study aims to prove that the ethanol extract of red beetroot (Beta vulgaris L.) has an effect on increasing FSH levels among female white rats (Rattus norvegicus) exposed to cigarette smoke. This was a True Experimental study with the post-test only control group design. The current study involved 25 female rats which were assigned into 5 groups: negative control, positive control, treatment I, II and III. The doses of red beetroot extract used were PI (125 mg/kgBW/day), PII (250 mg/kgBW/day), and PIII (500 mg/kgBW/day). Data were analyzed using One Way ANOVA with p-value of FSH (p = 0.000). The results of the study proved that administration of red beetroot ethanol extract at a dose of 500 mg/kgBW/day could increase the ovarian FSH levels among female rats exposed to cigarette smoke.